The effect of pulsed electric field pre-treatments prior to deep-fat frying on quality aspects of potato fries. (May 2015) - Ignat, Alexandra; Manzocco, Lara; Brunton, Nigel P.; Nicoli, Maria Cristina; Lyng, James G.
Abstract: The effect of pulsed electric fields (PEF) on potatoes intended for deep-fat frying was investigated. Potato cubes were submitted to 18.9 kJ/kg PEF treatments by applying 9000 pulses at 0.75 kV/cm electric field or 810 pulses at 2.50 kV/cm electric field. Regardless of the process conditions applied, PEF treatments increased moisture and softened potato cubes with no modification on their fresh-like appearance. Potato cubes submitted to PEF also showed a lower oil uptake upon frying than blanched and water-dipped controls. These effects were attributed to the structural modification of potato tissue upon PEF-induced electroporation. The latter could also favour leaching of reducing sugar from potato cubes surface, accounting for a lower browning tendency during frying. Industrial relevance: PEF technology could reduce chemical use, process time, water and energy consumption in potato fries production. It could also allow mass transfer to be controlled during frying, improving product colour and reducing oil uptake. Highlights: Potato cubes intended for deep-fat frying were pre-treated by pulsed electric fields. PEF treatments increase moisture and soften potato cubes. Potato cubes submitted to PEF showed low oil uptake upon frying. PEF treatments allow to lower the browning tendency of potato cubes during frying.